2010
DOI: 10.1007/s00213-010-2074-6
|View full text |Cite|
|
Sign up to set email alerts
|

Noise benefit in prepulse inhibition of the acoustic startle reflex

Abstract: Prefrontal dopamine transmission is altered in SH rats during the sensorimotor gating task of PPI of the acoustic startle, indicating increased dopamine reuptake in this ADHD rat model. We propose that noise benefit could be explored as a non-pharmacological alternative for treating neuropsychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…From this it can possibly be concluded that the higher the task demands are the more appropriate dopamine levels are required for a high performance [48]. Although noise is not found to increase dopamine levels per se, it looks like external noise in the nervous system acts in a similar fashion as dopamine release [49].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…From this it can possibly be concluded that the higher the task demands are the more appropriate dopamine levels are required for a high performance [48]. Although noise is not found to increase dopamine levels per se, it looks like external noise in the nervous system acts in a similar fashion as dopamine release [49].…”
Section: Discussionmentioning
confidence: 85%
“…Alternatively it is possible that their performance deteriorates because they just find the noise annoying and distracting. This possibility needs to be investigated in future research using human and animal models, directly measuring known neural and physiological markers of arousal in experiments employing manipulations of alternative factors (event rate or stimulant medication) known to change energetic levels [49], [51][62].…”
Section: Discussionmentioning
confidence: 99%
“…Prepulse inhibition (PPI) of the acoustic startle reflex refers to the reduction in the magnitude of the startle reflex when a loud startling stimulus (termed the “pulse”) is preceded by a quieter nonstartling stimulus (termed a “prepulse”) at short stimulus onset asynchronies [69], and represents an operational measure of sensorimotor gating [70], [71]. However, other studies have been shown that PPI is not a completely automatic process; it occurs involuntarily but can be modulated by controlled attentional processes and has been used as a tool for investigating attention [72], [73].…”
Section: Discussionmentioning
confidence: 99%
“…Although acoustic noise is not found to increase dopamine levels per se , it looks like external noise in the nervous system acts in a similar fashion as dopamine release, indicated by findings from a rat model of ADHD (Pålsson et al, 2011). As further support for the SR view a recent study showed neurophysiological effects on EEG/ERP of noise exposure during a GoNogo task where the P300 signal increased in the children that did benefit from noise (Baijot et al, 2016).…”
Section: Discussionmentioning
confidence: 95%